The impact of daily troponin-I and D-dimer serum levels on mortality of moderate-to-severe COVID-19 pneumonia patients. (14th October 2021) - Stavileci, B; Ozdemir, E
Abstract: Introduction: Coronavirus Disease 2019 (COVID-19) caused by that infection resulted in a very high morbidity and mortality rates globally. Purpose: The aim of this study is to analyses the daily Troponin-I and D-dimer levels and their impact on the need for intensive care and mortality of the COVID-19 infected patients. Methods: 206 patients who were hospitalized between 20.03.2020–05.05.2020 with a diagnosis of moderate-to-severe COVID-19 pneumonia were analyzed retrospectively. Serum Troponin-I and D-dimer levels were recorded at least 10 days. Results: Average age was higher in mortality group compared to non-mortality group (respectively 67.79±14.9, 56.87±18.15, p:<0.001). Presence of hypertension, diabetes mellitus, previous coronary bypass surgery, heart failure, chronic renal failure and chronic obstructive pulmonary disease were statistically significant affecting mortality (respectively p:0.003, p:0.004, p:0.045, p:0.02, p:0.003, p:0.007). First 10 days measurements of Troponin-I and D-dimer values was associated with mortality and intensive care requirement (p<0.001). Both Troponin-I and D-dimer were higher in mortality group compared to the patients requiring intensive care. Troponin-I value on the 7th day ≥16.05 pg/ml was related with need for intensive care (AUC: 0.896, sensitivity: %78.6, specificity: %78.3, p<0.001). Troponin-I value ≥30.25 pg/ml on the 9th day was related with mortality (AUC: 0.920, sensitivity: %89.5, specificity: %89.3, p<0.001). D-dimer value ≥878 hg/ml on the 2nd day was associated with intensive care need (AUC: 0.896, sensitivity: %78.6, specificity %78.3, p<0.001). D-dimer value ≥1106 hg/ml on the 10th day was associated with mortality (AUC: 0.817, sensitivity: %68.4, specificity: %65.2, p<0.001). It was observed that hospitalization periods ≥9.5 days were associated with mortality (AUC: 0.738, sensitivity %68.4, specificity: %65.9, p<0.001). Conclusion: We observed that hospitalizations ≥9.5 days increased mortality. Troponin-I and D-dimer follow-ups in serum are more effective than other inflammatory markers to show the need for intensive care and mortality. A high Troponin-I value should alert the clinician in terms of clinical deterioration. FUNDunding Acknowledgement: Type of funding sources: None.